Adaptation Strategies for Managing Climate and Environmental Risks while Pursuing Sustainable and Competitive Livelihoods: Experiences from AMIA Villages - Department of Agriculture; International Institute of Rural Reconstruction (2020)
The experiences of implementers of the AMIA Village approach, the Department of Agriculture’s Adaptation of the Climate Smart Village Approach identified a portfolio of 9 major strategies for pursuing resilience of agri-fishery sectors in the Philippines: 1. agricultural diversification, 2. Climate resilient crops, 3. Sustainable mechanization, 4. Enterprise development, 5. Climate information services, 6. Soil and water management, 7. Farmers database, 8. Learning platform, and 9. Agricultural financial services.